PENGARUH DAMPAK PANDEMI COVID-19 TERHADAP MINAT MENGAJUKAN PINJAMAN KREDIT PADA CUM CARITAS HKBP PEMATANGSIANTAR - Calen Calen; Beatrice Nathania; William Liang (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
This study aims to determine the effect of the impact of the Covid-19 pandemic on the interest in applying for credit loans at CUM Caritas HKBP Pematangsiantar. The research variable x is the impact of Covid-19 and the variable y is the interest in applying for a credit loan. In this study, the sampling technique was carried out by purposive sampling where the sample data collection method was by selecting subjects based on criteria predetermined by the researcher. The population of this research is all members of CUM Caritas HKBP Pematangsiantar during January to July 2019-2020 as many as 520 members, the sample is the special criteria for members who make loans (daily) who actively borrow from January to July 2019-2020 with a total of 80 people. . Data collection techniques used questionnaire techniques, interviews, observation. Data analysis used simple regression analysis program SPSS (Statistic Product and Service Solution) 24 For Windows. Based on these results, it shows that the Impact of the Covid-19 Pandemic has a significant negative effect on the Interest in Applying for Credit Loans at CUM Caritas HKBP. The regulations and performance of CUM Caritas HKBP affect the interest of members to apply for credit loans, not only the Covid-19 impact factor. So it is suggested for further researchers to conduct extensive research and add other variables that affect the interest of members in applying for credit loans.